Antioxidative defense system differences to drought stress of tomato cultivars - AYAN, ALP; ATAK, ÇİMEN; ÇELİK, ÖZGE (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
The aim of this study is to investigate the enzymatic and non-enzymatic responses of two different industrial tomato varieties (X5671R and 5MX12956) against drought stress. Fourteen-day-old seedlings were subjected to drought stress by non-watering and the stress was continued for 7 days. The effects of drought stress on tomato varieties analysed due to the results of biochemical analysis (total protein content, lipid peroxidation, relative water content, chlorophyll contents) and enzymatic activity and isozyme analysis of SOD, CAT, APX and POX. The highest water loss was recorded in X5671R as 73.17%. 64% total chlorophyll decrease was observed in both varieties on 7th day. Total protein, proline, malondialdehyde concentrations and antioxidant enzymes presented increase with related to increasing drought stress for both varieties. Due to the results, we concluded that 5MX12956 variety is more drought tolerant then X5671R. Isozyme densities and band differences were recorded. The densities of POX isozymes were started to increase from 5th day of stress. Fe-SOD, Cu/Zn-SOD1-2 isozyme bands were identified in X5671R variety, while 5MX12956 showed only Cu/Zn-SOD isozyme band. Differences in APX isozymes were observed from the 4th day of drought stress in both varieties. The results indicated the differences in antioxidant metabolism of tomato plants.
Keywords: Biotechnology; Applied Microbiology